The Determinant of Corporate Social Responsibility (CSR): The Role of Green Accounting as Moderating Variable in Indonesia - Rahman, Taufikur (Shafin: Sharia Finance and Accounting Journal, 2024)
This study aims to determine the role of Green Accounting in the relationship between environmental performance and Disclosure of Corporate Social Responsibility (CSR) in JII 70 Companies for the 2018-2020 period. This research is a type of quantitative research and the data in this research is secondary data in the form of panel data sampling technique with purposive sampling technique. The samples used were 24 companies registered on JII 70 for the 2018-2020 period. The data collection method is carried out by accessing financial reports and annual reports which can be accessed through the website www.idx.co.id. The data is processed using the Eviews10 analytical tool. The analytical method used is a descriptive test, stationarity test, regression model test, classical assumption test, t-test, F test, and MRA test. The results showed that the environmental performance variable has a positive and significant effect on the disclosure of Corporate Social Responsibility. The green accounting variable has a positive and insignificant effect on the disclosure of Corporate Social Responsibility. After conducting the MRA test it shows that the green accounting variable cannot moderate the effect of Environmental Performance on Disclosure of Corporate Social Responsibility.